The Legal Protection for Security Crowdfunding Based on Sharia Investment in MSMEs Economic Recovery - Winda Fitri (UNISSULA, 2023)
The security crowdfunding (SCF) provides collective fundraising services for MSMES who have difficulty obtaining funding without collateral based on OJK Regulation No. 16/POJK.04/2021, the SCF investment rules above don’t explicitly discuss investment activities in sharia-compliant securities for halal business financing that are free from Riba, maysir, and gharar elements. The purpose of this research is to examine the sharia economic legal protection for SCF investment contract transaction model and its legal implications in case of invalidity. This research uses a conceptual normative legal approach with a descriptive qualitative analysis. The results show that the contract activities in halal MSMES crowdfunding investment transactions have not fulfilled the principles of the Syirkah akad based on the Sharia Economic Law Compilation, which is from the expression side, the occurrence of ijab qabul (offer and acceptance) is not clearly in accordance with sharia, so the SCF contract can be invalidated and all activities related to the transaction are considered haram. Therefore, an issuer from DSN MUI is needed to guarantee that the SCF complies with sharia principles and has a sharia compliance officer.